Applications of landscape genetics in conservation biology: concepts and challenges - Segelbacher, Gernot; Cushman, Samuel A; Epperson, Bryan K; Fortin, Marie-Josée; Francois, Olivier; Hardy, Olivier J; Holderegger, Rolf; Taberlet, Pierre; Waits, Lisette P; Manel, Stéphanie (Conservation genetics, 2010)
Landscape genetics plays an increasingly important role in the management and conservation of species. Here, we highlight some of the opportunities and challenges in using landscape genetic approaches in conservation biology. We first discuss challenges related to sampling design and introduce several recent methodological developments in landscape genetics (analyses based on pairwise relatedness, the application of Bayesian methods, inference from landscape resistance and a shift from population-based to individual-based analyses). We then show how simulations can foster the field of landscape genetics and, finally, elaborate on technical developments in sequencing techniques that will dramatically improve our ability to study genetic variation in wild species, opening up new and unprecedented avenues for genetic analysis in conservation biology.